Mosque Youth Groups Empowerment and Disaster Risk Reduction in Soka Hamlet, Bantul - Yordan Gunawan; Muhammad Endrio Susila; Zulfiani Ayu Astutik; Tri Anggoro Putro (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Soka Hamlet is one of the villages in Seloharjo, Pundong District, Bantul Regency, Yogyakarta Special Region. Almost 80% of the residential areas in Soka were destroyed and leveled to the ground due to the 2006 earthquake, and nearly all residents are still traumatized. Lack of training and dissemination on natural disasters, and emergency response, especially earthquakes, has become a problem for most societies when an earthquake occurs. This community service uses an educational approach oriented to the problem-solving process. By using participatory training and education methods that are carried out in a systematic, directed, and planned manner with the active participation of individuals, groups, and the community as a whole, this activity is expected to be able to provide an understanding to the community regarding natural disaster management and preparedness to deal with them, while participatory is an approach that emphasizes on efforts to increase the participation of the community or individuals directly in various processes and program implementation. The results of the service program are shown by the formation of a mosque youth group that is aware of and has a good response to natural disaster situations.